Implementation of Village Fund Policy in Puse, South Dampal District, Tolitoli Regency - Kurnia, Intam; Rachmad, Rachmad; Farista, Gita; Akbar, Akbar (Journal of Management and Administration Provision, 2024)
This research was conducted in Puse Village, South Dampal District, Tolitoli Regency, with the aim of determining the implementation of village fund policies in Puse Village, South Dampal District, Tolitoli Regency. This research uses qualitative descriptive research using Edward III's policy theory with four aspects, namely communication, resources, disposition, and bureaucratic structure. In this study, the author used a purposive technique, namely by selecting people who are considered to understand the problem being studied. Based on the results of the study, it shows that the implementation of village fund policies in Puse Village is good but needs to be improved, where three of the four aspects of the policy that have been implemented are Disposition, resources, and bureaucratic structure, while the Communication aspect has not been implemented properly where the process of socializing village fund policies carried out by Puse village officials only involves a small part of the community, so that many people still do not understand the direction and objectives of village fund policies, as well as the lack of information on the use of village funds through bulletin boards or other media.